Tobacco‐free policy reduces combustible tobacco byproduct on a large university campus. Issue 1 (5th December 2022) - Gelino, Brett W.; Salzer, Allyson R.; Harsin, Joshua D.; Naudé, Gideon P.; Gilroy, Shawn P.; Reed, Derek D.
Abstract : Policy drives community‐level behavior change, so behavior analysts should aid empirical policy development. University campus regulation is a useful proxy for broader policy initiatives and thus is a convenient inroad for behavior analyst involvement. This paper examines behavior analytic contributions to the planning and evaluation of a university tobacco‐free initiative. We provided resources and guidance throughout early planning, and we then evaluated faculty and student compliance via byproduct (e.g., cigarette butts) counts taken at four high‐traffic sites (as flagged by preliminary surveying of campus faculty, staff, and students). Visual analysis and supplementary statistical testing support notions of (a) a meaningful and sustained reduction of combustible tobacco byproducts in all locations, and (b) a demonstrative example of behavior analytic involvement with university policy planning and evaluation.